2010
DOI: 10.1016/j.jcrs.2010.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of toxic anterior segment syndrome from generic trypan blue

Abstract: We report 2 cases of toxic anterior segment syndrome (TASS) resulting from impurities in generic trypan blue that was administered intracamerally to improve visualization of the capsule. Histology of the corneal buttons revealed foci of inflammatory response and complete loss of endothelial cells. Cell culture analysis showed that the generic trypan blue was approximately twice as toxic to the endothelium as a proprietary trypan blue. Ophthalmologists should be aware that any substance administered intraocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 25 publications
0
16
0
5
Order By: Relevance
“…When the concentration was increased to 0.05%, viability decreased by 55% with generic TB, and by 30% with the proprietary TB. A study performed using corneal fibroblasts and endothelial cells in human donor eyes demonstrated a TB-induced dose-dependent cytotoxic effect after incubation times of up to 24 h. High TB concentrations and long incubation times have also been shown to exhibit significant cytotoxicity in human cultured corneal endothelial cells (14,25) . Given these findings, controversy exists over whether TB is safe for corneal tissue.…”
Section: Resultsmentioning
confidence: 99%
“…When the concentration was increased to 0.05%, viability decreased by 55% with generic TB, and by 30% with the proprietary TB. A study performed using corneal fibroblasts and endothelial cells in human donor eyes demonstrated a TB-induced dose-dependent cytotoxic effect after incubation times of up to 24 h. High TB concentrations and long incubation times have also been shown to exhibit significant cytotoxicity in human cultured corneal endothelial cells (14,25) . Given these findings, controversy exists over whether TB is safe for corneal tissue.…”
Section: Resultsmentioning
confidence: 99%
“…2,[10][11][12][13] Literatürde kapsüloreksis öncesi tripan mavisi kullanımının kornea endoteline etkisini araştıran pek çok çalışmaya rastlanmaktadır. [14][15][16][17][18] Çalışmaların çoğunda ortak görüş endotel toksisitesinin az olduğu yönündedir. Örneğin, bu çalışmalardan birinde %0,6 oranındaki tripan mavisinin 1 yıllık takipte kornea endotel hasarı yapmadığı, bir diğerinde ise %0,1'lik tripan mavisinin 8 yıllık takipte endotel toksisitesi yapmadığı bildirilmektedir.…”
Section: Discussionunclassified
“…68 Perhaps the most serious reported complications of TB have been a report of two cases of toxic anterior segment syndrome (TASS) leading to irreversible endothelial damage. 69 TB has also been reported to cause a sterile endophthalmitis in 3 out of 17 cases where a single batch of TB 0.6 mg/ml was used. 70 It was commented that the dye was from an unknown commercial manufacturer, with a contaminant suspected to be the causative agent.…”
Section: Safetymentioning
confidence: 98%